Toxicidades gastrointestinales relacionadas a la inmunoterapia o inhibidores de puntos de control inmunitarios o del checkpoint - Villanueva O., Luis (Revista Hospital Clínico Universidad de Chile, 2024)
Immune checkpoint inhibitors have revolutionized cancer therapy by enhancing the immune system’s ability to target tumor cells. However, these therapies can cause immune-related adverse events (irAEs), particularly in the gastrointestinal tract, leading to conditions like colitis and diarrhea. The incidence and severity of these irAEs vary depending on the type of inhibitor and patient-specific factors, with higher rates observed in combination therapies. The pathophysiology includes the underlying mechanisms of irAEs, histological findings, and animal models in colitis induced by immune checkpoint inhibitors (ICIs), as well as the influence of the gut microbiome. Early diagnosis and effective management, including corticosteroids and selective immunosuppressants, are crucial. Keywords: , , , ,